marry-tot, the (1971)
marry-tot, the This is the term used in my area to name the bone of a bird, located where its neck is connected to the breast-bone. When we were boys my brother and I used to break this bone to see who would be married first. Each of us would place out thumbs together at the top of the "marry-tot" . . . See cited quotation. JH 6/71 Not used Not used Withdrawn [see 'rocky bone'] 'marry bone( 'wish-bone' master card] 'merry thought', 'merry taught']